Wi-Fi: The access road - Hasson, Amir A. (Technical Centre for Agricultural and Rural Cooperation, 2008)
By using existing roads and communication systems, rural communities in Rwanda can connect to the internet through passing buses, cars or motorbikes fi tted with Wi-Fi.